DETEKSI ERGOSTEROL SEBAGAI INDIKATOR KONTAMINASI CENDAWAN PADA TEPUNG TERIGU [Ergosterol Detection as an Indicator of Fungal Contamination in Wheat Flour] - A. Rika Pratiwi; Anjarsari . (Jurnal Teknologi dan Industri Pangan, 2002)
Fungal contamination of foodstuffs or foods during the storage period is becoming a serious matter. Quantification method is needed for qualifyng storage method and its evaluating contaminant so that a quick fungal and its metabolite detection can be used to prevent further contaminantion. One detecting method was measuring ergosterol content. Ergosterol is a sterol group compound, which is a contituting component of specific membrane on fungi and it does not exist on other microorganisms. The objective of the research is to describe fungi contamination in wheat flour during the storage period based on its ergosterol content. Ergosterol evaluation and microbiological evaluation are aimed to determine the content of ergosterol and to determine fungal species. Ergosterol content is measured by HPLC and fungal species is determined by the isolation and microscopic identification. The result of this research is fungal contamination can be detected by ergosterol eveluation and microbiological. The lowest detected ergosterol content was 0.211 ppm. Ergosterol content increased significanly during storage period which indicates that fungal contaminant level increased is well. The determined fungi species were found in high and low gluten of wheat flour which were potential to produce mycotoxin.